A clinical study to evaluate the cardiopulmonary characteristics of two different anaesthetic protocols (tiletamine/zolazepam ± medetomidine) and to evaluate their suitability for immobilization of healthy chimpanzees - Strong, Victoria; Möller, Torsten; Tillman, Ann-Sofie; Träff, Stefan; Guevara, Louise; Martin, Mike; Redrobe, Sharon; White, Kate (Wiley, 2018)
Objective: To characterise the cardiopulmonary characteristics of two different anaesthetic protocols (tiletamine/zolazepam +/- medetomidine) and their suitability for the immobilisation of healthy chimpanzees undergoing cardiac assessment. Study design: Prospective, clinical, longitudinal study Animals: Six chimpanzees (Pan troglodytes) aged 4 - 16 years weighing 19.5 - 78.5 kg were anaesthetized on two occasions Methods: Anaesthesia was induced with tiletamine/zolazepam (TZ) (3-4 mg kg-1) or tiletamine/zolazepam (2 mg kg-1) and medetomidine (0.02 mg kg-1) (TZM) via blow dart (IM) and maintained with intermittent boluses of ketamine (IV) or zolazepam/tiletamine (IM) as required. The overall quality of the anaesthesia was quantified based on scores given for: quality of induction, degree of muscle relaxation and ease of intubation.  The time to achieve a light plane of anaesthesia, number of supplemental boluses needed and recovery characteristics were also recorded. Chimpanzees were continuously monitored and heart rate (HR), pulse rate (PR), respiratory rate (fR) oxygen saturation of heamoglobin (SpO2), systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), rectal temperature, mucous membrane colour and capillary refill time recorded. During the first procedure (TZ) animals underwent a 12 channel ECG, hematology, biochemistry and cardiac biomarker assessment to rule out the presence of pre-existing cardiovascular disease. A detailed echocardiographic examination was carried out by the same blinded observer during both procedures. Data were compared using Student’s paired t-test or Wilcoxon rank tests as appropriate. Results: There was a significant difference for the area under the curves between anaesthetic protocols for HR, SAP, MAP and fR. No significant differences in the echocardiographic measurements were evident. Quality of anaesthesia was significantly better with TZM and no additional boluses were required. The TZ protocol required multiple supplemental boluses. Conclusions and clinical relevance: Both combinations are suitable for immobilization and cardiovascular evaluation of healthy chimpanzees. Further work is required to evaluate the effect of medetomidine in cardiovascular disease.